Smart Tourism Intermingling with Indian Spiritual Destinations: Role of e-WoM Sentiments in marketing - Senthil Veerasamy; Susobhan Goswami (ASEAN Journal on Hospitality and Tourism, 2022)
The purpose of this study is to see how smart tourism and sentiments help tourists seeking spiritual experiences that are deep-rooted in ancient Indian traditions as opposed to materialistic getaways. Exploratory research through sentiments of YouTube and Tweets followers are collected in sample. A qualitative-quantitative research method is used in this paper to analyse the sentiments on Indian popular spiritual destinations. Smart tourism allows larger, coordinated efforts for Innovation, quality of life and sustainable tourism through rich data infrastructure within the ambit of specific destinations. Within a context, personalisation and real-time monitoring can occur where sentiments are positive or highly positive for that matter. Fundamental to tourists’ experiences is an aesthetic obsession with authenticity. The diversity of smart technologies applicable to experiences in the smart spiritual tourism sphere is still to be defined on a more granular level where religion still holds the glue. This paper seeks to explore the smart tourism experience concept applied to spirituality (STES) in more depth to facilitate further contributions. A smart tourism experience can be co-created for better delivery and a conducive environment for such an experience to emerge. Each spiritual destination is unique and complex. Policy responses can address the impact mainly through knowledge (human) resources.